Socialist De-Colony - Osei-Opare, Nana (Cambridge University Press, 2026)
In 1957, Ghana won its political independence from the United Kingdom. Nana Osei-Opare offers a provocative reading of this defining moment. He demonstrates how race and Soviet influence enabled and disrupted Ghana's transformational projects to secure Black freedom. This title is also available as open access on Cambridge Core.